2012
DOI: 10.1186/1477-7827-10-57
|View full text |Cite
|
Sign up to set email alerts
|

Malformations in a cohort of 284 women with Mayer-Rokitansky-Küster-Hauser syndrome (MRKH)

Abstract: BackgroundThe aim of this retrospective study was to describe the spectrum of genital and associated malformations in women with Mayer-Rokitansky-Küster-Hauser syndrome using evaluated diagnostic procedures and the Vagina Cervix Uterus Adnex – associated Malformation classification system (VCUAM).Methods290 women with MRKH syndrome were clinically evaluated with using clinical examinations, abdominal and perineal/rectal ultrasound, MRI, and laparoscopy.ResultsClassification of female genital malformation accor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
103
5
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(124 citation statements)
references
References 19 publications
12
103
5
4
Order By: Relevance
“…Fat in the ischiorectal fossa (F) is seen lateral to the rectum. but normal uterus, as in our patient (2,9). In a two-center retrospective analysis, probably the largest, of 290 women who were categorized in accordance with the VCUAM classification (5), not a single case was found to have a normal uterus (5,9).…”
Section: Discussionsupporting
confidence: 51%
“…Fat in the ischiorectal fossa (F) is seen lateral to the rectum. but normal uterus, as in our patient (2,9). In a two-center retrospective analysis, probably the largest, of 290 women who were categorized in accordance with the VCUAM classification (5), not a single case was found to have a normal uterus (5,9).…”
Section: Discussionsupporting
confidence: 51%
“…Oppelt et al reported a cohort of 284 women with MRKH syndrome, only 0.7 % of whom presented with a hypoplastic uterus. None of them had a normal-sized septate uterus [15].…”
Section: Discussionmentioning
confidence: 99%
“…Современные критерии синдрома МРКХ вклю-чают: аплазию матки и влагалища, первичную аме-норею, развитые по женскому типу вторичные поло-вые признаки, неизмененные яичники и женский кариотип 46ХХ (MIM 277000) [4][5][6]. Синдром МРКХ выявляется у 10% женщин с первичной аменореей [7].…”
unclassified
“…Наиболее часто при аплазии влагалища и матки встречаются сопутствующие пороки развития верх-ней части мочевыделительной системы -примерно 29-40% всех пациенток с аплазией влагалища и мат-ки [4,11,12] и позвоночника -у 30-40% пациенток [13,14]. Аномалии развития почек включают одно-стороннюю аплазию, эктопическое расположение одной или обеих почек, подковообразную почку, ги-дронефроз и даже аплазию обеих почек [12,15].…”
unclassified